2017
DOI: 10.7602/jmis.2017.20.3.84
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approach to Supra-pubic and Non-Midline Lower Abdominal Ventral Hernia - An Extended Indication of TAPE Technique

Abstract: Repair of lower abdominal incisional hernia is always a surgical challenge. TAPE technique has been described for the repair of supra-pubic midline incisional hernia with satisfactory outcome. Its indication can be extended for treatment of non-midline lower abdominal hernia. Peritoneal incision is created just below the hernia defect with pre-peritoneal dissection to expose supra-pubic preperitoneal space with Cooper's ligament exposed. Non-adhesive mesh then placed over preperitoneal space and partially intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…(2) erect position; and (3) the fact that this area represents the weakest point of the abdominal wall (1,9,13). In our study, the recurrence rate was 2.9% (2/68 cases) with no statistical significance between the two groups seen through follow-up investigations.…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…(2) erect position; and (3) the fact that this area represents the weakest point of the abdominal wall (1,9,13). In our study, the recurrence rate was 2.9% (2/68 cases) with no statistical significance between the two groups seen through follow-up investigations.…”
Section: Discussioncontrasting
confidence: 58%
“…Based on these factors, the optimization of approaches to hernial procedures have become a hot topic in the surgical field. Previous reports have indicated that the TAPE technique significantly reduces the recurrence rate and mesh-induced complications of suprapubic incisional hernia (13)(14)(15). However, closing the peritoneal flap during TAPE prolongs the operative time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations